E-Customer Review, E-Customer Rating, and E-Payment: Perspective Differences between Generation Y and Z - Paras Islami; Virgo Simamora (Journal Of Social Science (JoSS), 2023)
E-commerce can use E-Customer Reviews, E-Customer Ratings, and E-Payments as important features to attract consumers to buy from e-commerce. This study examined the perspectives' differences between Generation Y and Generation Z on online reviews, ratings, and payments. Generation Y and Generation Z, who live in Jakarta and have shopped online more than once, are the populations of this study. To get a representative sample for this research, the method of purposive sampling was employed. A questionnaire was used as the data collection technique, and it was sent out over the internet to Generation Y and Generation Z who satisfied the criteria set out for this research. In all, there were 170 of Generation Y and 170 of Generation Z that took part in this study. The data is analyzed using the program SPSS version 27, and the study results indicate that there are differences in the perspectives of Generation Y and Generation Z about e-customer reviews, e-customer ratings, and e-payments.